2017
DOI: 10.1021/acs.jnatprod.6b00923
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Quantitative Measures in NMR: Quantum Mechanical qHNMR Advances Chemical Standardization of a Red Clover (Trifolium pratense) Extract

Abstract: Chemical standardization, along with morphological and DNA analysis ensures the authenticity and advances the integrity evaluation of botanical preparations. Achievement of a more comprehensive, metabolomic standardization requires simultaneous quantitation of multiple marker compounds. Employing quantitative 1H NMR (qHNMR), this study determined the total isoflavone content (TIfCo; 34.5–36.5% w/w) via multimarker standardization and assessed the stability of a 10-year-old isoflavone-enriched red clover extrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
70
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(71 citation statements)
references
References 38 publications
1
70
0
Order By: Relevance
“…The identification of the semi‐preparative HPLC and HSCCC peaks was based on the LC retention time and on the ESI‐MS, 1 H‐NMR, and 13 C‐NMR spectra. The 1 H‐NMR and 13 C‐NMR data are given in the Supporting Information and were found to be in good agreement with those of the corresponding compounds in the literature .…”
Section: Resultssupporting
confidence: 79%
“…The identification of the semi‐preparative HPLC and HSCCC peaks was based on the LC retention time and on the ESI‐MS, 1 H‐NMR, and 13 C‐NMR spectra. The 1 H‐NMR and 13 C‐NMR data are given in the Supporting Information and were found to be in good agreement with those of the corresponding compounds in the literature .…”
Section: Resultssupporting
confidence: 79%
“…This review identified a multitude of rationales, why and how raw NMR data can provide useful and/or unprecedented insights. Presented cases exemplify the importance of sharing raw NMR data in NP research and fall into seven areas of broader impact: (i) the enhancement of the integrity of structure elucidation, which has major implications on downstream activities; (ii) the ability to document the purity status of a given material and enable future meta-analysis and/or refinement of the evaluation; notably, the (semi-)quantitative evaluations are often feasible even if the more rigorous conditions of quantitative NMR (qNMR)29,389391 were not satisfied during data acquisition, and even if no internal calibration was used (feasibility of the 100% qNMR method);29,390 (iii) the enhancement of the accuracy and general capabilities of dereplication methods, thereby addressing one of the major challenges in metabolomics; (iv) enhancement of the amount of information obtained from NMR spectra and the speed of the mining process, by employing newly emerging software tools that depend on the availability of larger data sets; (v) the catalysis of developments in the field of the less studied NMR-accessible nuclei, offering new opportunities for the study of NPs and their analogues, of these fields; (vi) the promotion of the proven capabilities of existing repositories; (vii) the prospects of extending NP and metabolomic knowledge into clinical applications, e.g. , by using magnetic resonance spectroscopy (MRS).…”
Section: Discussionmentioning
confidence: 99%
“…The isoflavone content of four dietary supplements has been determined by HPLC, qNMR, and 2D 1 H DOSY NMR. The quantification of these compounds is generally carried out by HPLC or qNMR [29][30][31][32]. However, the use of 2D 1 H DOSY NMR allowed the detection of various components of these formulations in a single run.…”
Section: Discussionmentioning
confidence: 99%